النقل البري الداخلي و الخارجي للركاب و مشكلاته التسويقية في سورية - صقر محمد; برهوم أديب; معروف حيدر حسن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تناولت هذه الدراسة واقع النقل البري الداخلي و الخارجي للركاب و مشكلاته التسويقية في سوريا من خلال البحث في مجالين أساسيين هما: المجال الأول: النقل البري الداخلي و الخارجي في سوريا. حيث تضمن دراسة واقع النقل البري من خلال جمع المعلومات و البيانات عن تطور أطوال الطرق البرية و أعداد وسائط النقل الطرقي ودراسة معادلات الاتجاه العام لهذه المتغيرات والعلاقات التي تربط بينها بالإضافة إلى تطور أطوال السكة الحديدية. وأعداد القطارات و العربات خلال عشر سنوات, وكذلك دراسة مدى مساهمة أشكال النقل البري في نقل الركاب الداخلي و الخارجي في سوريا بشقيه النقل الطرقي و النقل عن طريق السكة الحديدية, و ذلك من خلال استعراض الطاقات النقلية المتوفرة يوميا للنقل العام المأجور ودراسة تطور أعداد الركاب المنقولين براً. المجال الثاني: يتناول المشاكل التسويقية للنقل البري في سوريا من خلال البحث في أهم هذه المشاكل و هي الأسعار و كيفية تحديدها بالإضافة إلى المنافسة و سلبياتها، وكذلك الإعلان وآثاره و القوانين و الأنظمة و طرق الحجز و السفر. وقد توصلنا إلى نتائج هامة، يمكن أن تساهم في تطوير النقل البري للركاب في سورية وتحديثه وتفعيله، وفي دفع عجلة التنمية نحو الأمام. This study deals with the fact of interior and exterior land transportation of passengers and its marketing problems in Syria, through discussing them in two basic fields. The first field is about the interior and exterior land transportation in Syria. So that it includes studying the fact of land transportation through out collecting the information and data about the development of land roads lengths, the numbers of road transportation means, studying the proportion of general trend for these variables, the relation ships which connect each othor the development of railway lengths, the numbers of trains and carriages during ten years, also studying the extent of land transportation forms contributing in transporting the passengers inside and outside Syria with both kinds: the road transportation and the transportation by means of railway, through displaying the daily transport powers available for the paid public transportation, and studying the numbers of passengers conveyed by land. The second field deals with marketing problems of the land transportation in Syria through discussing the most important of those problems which are: the prices, how to define them in eddition to the competition and its negatives also the advertisement and its effects, the laws, the regulation the reservation ways, and the travel. We have got important results which may contribute in developing, regenerating and activating the land transportation of passengers in Syria, also in pushing the development wheel forward.